Role of declining discharge and water pollution on habitat suitability of fish community in the Mathabhanga-Churni River, India. (1st December 2021) - Sarkar, Biplab; Islam, Aznarul; Chandra Das, Balai
Abstract: The present study examines the habitat suitability of three selected reaches of the Mathabhanga-Churni River in the wake of the declining river regime and escalating river water pollution. The study portrays the habitat degradation through the lens of the habitat suitability index (HSI) model based on four water quality (turbidity, pH, dissolved oxygen, and water temperature), three reproduction (pool velocity, riffle velocity, and riffle depth), and two food and cover (percentage vegetation cover and percentage pool) variables. Among the water quality variables, depletion in DO (0.4 mg/L) has become the most significant factor for fish habitat degradation. Reach-specific study of HSI reveals high habitat degradation for reach1 (RE1) and reach 2 (RE2) compared to reach 3 (RE3). The seasonality in HSI has also been reflected for all the study reaches. The value of HSI at RE1 depicts that 97.67% of samples of pre-monsoon season belong to the poor habitat category. Moreover, the study of fish species also reveals that the diversity and productivity have declined at a faster rate for RE1 and RE2 compared to RE3. For example, 29, 28, and 21 fish species have disappeared from RE1, RE2, and RE3 respectively since 1983. This typical habitat degradation is induced by lowering of discharge due to longitudinal disconnection of the Mathabhanga-Churni River from the Padma River due to the eastward tilting of the Bengal delta. Moreover, anthropogenic pollution such as discharge of industrial effluents, mixing of municipal sewage, pollutants from agricultural runoff are found to exacerbate habitat degradation. Finally, the study indicates few ways to restore the degraded fish habitat of the river. Graphical abstract: Image 1 Highlights: Habitat suitability is assessed in terms of water quality, reproduction and cover indicators. Pre-monsoon season exhibits the poor habitat compared to the monsoon and post-monsoon. The lower reach depicts good fish diversity and productivity compared to upper reach. A significant lowering of discharge, industrial water pollution and urban sewage drive habitat degradation.